2017
DOI: 10.1111/anu.12546
|View full text |Cite
|
Sign up to set email alerts
|

Effects of totally replacing dietary fish oil by linseed oil or soybean oil on juvenile hybrid sturgeon,Acipenser baeriBrandt×A. schrenckiiBrandt

Abstract: The growth performance, body composition, fillet fatty acid content, serum hepatic enzymes and postprandial changes in serum lipid metabolism of hybrid sturgeon (70.8 ± 0.5 g) were investigated to determine the effects of total replacement of 80 g kg -1 fish oil (diet A) with linseed oil (diet B) and soybean oil (diet C), respectively. No significant differences in weight gain rate and specific growth ratio were observed among all fish groups (p > .05). Diet A fish group had the highest, but diet B fish group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
23
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 50 publications
(72 reference statements)
3
23
2
Order By: Relevance
“…For juveniles and subadults of freshwater fish species, it has been demonstrated that essential fatty acid (EFA) requirements can be satisfied by the C18 PUFA, 18:3n‐3 and 18:2n‐6 (NRC, ). Liu et al () reported that juvenile hybrid sturgeon could well utilize linseed or soy oils without negative effect on growth. Deng, Hung, and Conklin () suggested that juvenile white sturgeon ( A. transmontanus ) require both n‐3 and n‐6 fatty acids, but not tested for other sturgeons, especially for the larval stage of related species (Hung, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For juveniles and subadults of freshwater fish species, it has been demonstrated that essential fatty acid (EFA) requirements can be satisfied by the C18 PUFA, 18:3n‐3 and 18:2n‐6 (NRC, ). Liu et al () reported that juvenile hybrid sturgeon could well utilize linseed or soy oils without negative effect on growth. Deng, Hung, and Conklin () suggested that juvenile white sturgeon ( A. transmontanus ) require both n‐3 and n‐6 fatty acids, but not tested for other sturgeons, especially for the larval stage of related species (Hung, ).…”
Section: Discussionmentioning
confidence: 99%
“…Low DHA but high EPA level in the broodstock diet may reduce spawning and larval quality of Siberian sturgeon (Luo et al, ). However, juvenile hybrid sturgeon ( A. baeri × A. schrenckii , body weight 78 g) could utilize linseed or soy oils as well as fish oil for growth (Liu et al, ). As a freshwater fish species, whether or not the Siberian sturgeon requires EPA or DHA, and the effects of DHA/EPA ratio during the early life are not known.…”
Section: Introductionmentioning
confidence: 99%
“…This plant oil with more than 55 million tons annual production in 2018 is the second top produced oil after palm oil. Price stability, high production and sustainability have made SO an excellent candidate for FO replacement in aquafeeds (Liu et al, ; Pontes et al, ; Turchini, Torstensen, & Ng, ). However, in all fish species such as ornamental fish, the source of oil in the diet plays a crucial role in increasing the number and quality of eggs and larvae and improving reproductive performances.…”
Section: Introductionmentioning
confidence: 99%
“…In general, freshwater fish have the ability to synthesize long chain polyunsaturated fatty acids (LC-PUFAs), utilizing ALA; thus, LO has become a potential high-quality substitution oil source 6,7 . Previous studies have shown that FO substitution by a suitable content of LO in the feed would improve the diet conversion rate of fish as well as fish health 612 .…”
Section: Introductionmentioning
confidence: 99%